THE IMPACT OF MOBILE PAYMENT SYSTEMS ON FINANCIAL INCLUSION IN DEVELOPING COUNTRIES - Bakoeva Gulbakhor (SCIENCE AND CULTURE: INNOVATIONS OF THE 21ST CENTURY, 2025)
This article explores how mobile payment systems contribute to financial inclusion in developing countries. It examines the mechanisms through which mobile technology improves access to banking services, reduces transaction costs, and empowers marginalized populations. The study also highlights challenges such as regulatory constraints, cybersecurity risks, and digital literacy barriers. Using empirical evidence from Africa, Asia, and Latin America, this paper demonstrates that mobile payment systems play a pivotal role in bridging the financial inclusion gap, driving economic growth, and reducing poverty.